A Comparative Study of K±/π± Ratio in Proton-Proton Collisions at Different Energies: Experimental Results versus Model Simulation - Swarnapratim Bhattacharyya; Maria Haiduc; Alina Tania Neagu; Elena Firu (Advances in High Energy Physics)
A detailed study of energy dependence of K+/π+, K-/π- and total kaon to pion multiplicity ratio K++K-/π++π-=K/π has been carried out in proton-proton (pp) collisions at s=6.3, 17.3, 62.4, 200, and 900 GeV and also at s=2.76 TeV and 7 TeV in the framework of UrQMD and DPMJET III model. Dependence of K+/π+ and K-/π- on energy shows different behavior for UrQMD and DPMJET III model. The presence of the horn-like structure in the variation of K+/π+ and K-/π- with energy for the experimental data is supported by the DPMJET III model. Experimentally it has been observed that as energy increases, the total kaon to pion multiplicity ratio K++K-/π++π-=K/π increases systematically for pp collisions at lower energies and becomes independent of energy in LHC energy regime. Our analysis on total kaon to pion multiplicity ratio K++K-/π++π-=K/π with UrQMD data is well supported by the experimental results obtained by different collaborations in different times. In case of DPMJET III data, the saturation of K/π ratio at LHC region has not been observed.